Chemical Composition and Nutritional Properties of Landraces Alfalfa (Medicago sativaL.) Cultivars - SENGUL, MERYEM; SENGUL, SULEYMAN (Asian Journal of Chemistry, 2010)
18 Landraces alfalfa cultivars were examined in a field experiment in year 2004. Adiguzel, Ahlat(2), Alaköy, Burcu, Çayirbasi(16), Dilburnu(6), Dönemeç(21), Ercis, Gülgören(23), Gülsinberk, Hidirkoy(13), Kasimoglu(11), Köprüler(12), Mahmudiye, Mollakasim(4), Otluca, Otluyazi(20). Crude protein (CP), dry matter (DM), K, Mg, Na, Cu, Mn and Zn, as a mineral concentration, neutral detergent fiber (NDF), acid detergent lignin (ADL) and acid detergent fiber (ADF) as a energy content were studied. A greater proportion of significant phenotypic variations were observed many genotypes. Considerable significant correlations in chemical concentrations between genotypes were measured. Amongst the characteristics examined in this experiment there are negative significant correlation observed between organic method (OM) with K (r = -0.358*), highly negative significant between NDF with DM (r = -0.881**), NEL (r = -0.465**), NEG (r = -0.449**) and TDN (r = -0.451**), between ADF with NEL (r = -0.997**) and NEG (r = -0.994**). Highly significant positive relationships were determined between NDF with ADF (r = 0.451**). There are highly positive significant correlation observed between OM with DM (r = 0.883**), NEL (r = 0.462**). This result suggest that Dilburnu (6), Mahmudiye, Otluca and Ovakisla cultivars should provide useful genetic material for enhancing mineral concentration in alfalfa forage. Variation could be exploited as an additional source of genetic variation in breeding programs for quality trials to achieve a higher genetic gain for breeding cycle.